A Minimizing Sequence Proof of the Banach Fixed Point Theorem - Bataihah, Anwar (Statistics, Optimization & Information Computing, 2025)
We present a novel proof of the Banach contraction mapping theorem based on minimizing sequences. By analyzing the set A = {d(x, T(x)) : x X} of point-to-image distances, we construct a sequence that converges to the unique fixed point. A key technical contribution is Lemma lemma1, which establishes an optimal inequality between contraction coefficients and the b-metric constant. We demonstrate applications to b-metric spaces and discuss extensions to incomplete metric spaces. Examples show the effectiveness of this approach, which provides a geometric alternative to classical methods.